Diversity of arterial cell and phenotypic heterogeneity induced by high-fat and high-cholesterol diet - Wen, Jieqi; Ling, Rongsong; Chen, Ruiyue; Zhang, Siyan; Dai, Yarong; Zhang, Tingtao; Guo, Fanyu; Wang, Qingxin; Wang, Guixin; Jiang, Yizhou (Frontiers in Cell and Developmental Biology, 2023)
Lipid metabolism disorder is the basis of atherosclerotic lesions, in which cholesterol and LDL are the main factors involved with the atherosclerotic development. High-fat and high-cholesterol diet can lead to this disorders in the human body, thus accelerating the process of disease. The mature of single-cell RNA sequencing recent years opens the possibility to unbiasedly map cellular heterogeneity with high throughput and high resolution, transcriptomic alterations mediated by a high-fat and high-cholesterol diet at the single-cell level then can be explored with this mean. We dissociate two control (12 weeks of chow diet) and two HFD (12 weeks of high fat, high cholesterol diet) aortic arch of 16-week Apoe-/- mice to process single cell suspension and use single-cell RNA sequencing to analyze the transcripts of 5416 cells from control group and 2739 from HFD one. Through unsupervised clustering, fourteen cell types were divided and defined. Among these cells, the cellular heterogeneity exhibited in endothelial cells and immune cells is the most prominent. Subsequent screening delineated ten endothelial cell subsets of different function based on gene expression profiling. The distribution of endothelial cells and immune cells differs significantly between control group versus HFD one. The existence of pathways that inhibit atherosclerosis was found in both dysfunctional endothelial cells and foam cells. Our data provide a comprehensive transcriptional landscape of aortic arch cells and unravel the cellular heterogeneity brought by high-fat and high-cholesterol diet. All these findings open new perspectives at the transcriptomic level to studying the pathology of atherosclerosis.